Seat Belt Use and Perceptions Among Inter-Urban Commercial Vehicle Drivers in Ilorin, Nigeria - Bolaji Abdulkadir Usman; Toluwase Adebosin (Journal of Road Safety)
Road traffic crash is a major cause of death and injuries in the world. Although, seat belts are designed to reduce the risk and severity of injury, its use is low in low- and middle-income countries. This research examined the usage and perception of seat belt among inter-urban commercial drivers in Ilorin, Nigeria (N = 135). Data were collected in a cross-sectional survey on demographic characteristics of the drivers, regularity of use of seat belt, reasons for use and non-use and perception of its benefits. Results showed that despite the recognition of the importance of seat belt by 90 percent of the drivers, the compliance rate was 40 percent and included only 6.6 percent who wore a seat belt for its safety implications. There was a significant difference in use of restraint by age (X^2^ (12) = 23.1, p= .005), with more seat belt use among older drivers. While the rate of compliance was highest among drivers with tertiary education, no significant difference was found between educational status and usage of seat belt. Main reasons for non-compliance are frequent stops and fear of being trapped after a crash. It is recommended that efforts be made to raise awareness and intensify enforcement to improve seat belt compliance.